Pengembangan Aplikasi Bebas Pustaka Mandiri dengan Menerapakan Model Integrasi Sistem dan Interoperabilitas - Andi Saputra; Leni Marsih (Media Pustakawan, 2023)
The Library Free Certificate (SKBP) is a graduation requirement that is applied in many universities, one of which is the Andalas University Library. To make it easier for students to get SKBP, the library has used the Bebas Pustaka Mandiri Application. This application is web-based and can be accessed online. Its development applies the interoperability model by integrating it with other related applications, namely: the Library Catalog Information System, and Graduation Information System. This application allows students to propose the issuance of SKBP independently without the need to come to the library. This study aims to test the performance and measure the benefits of implementing the Aplikasi Mandiri in overcoming various problems in SKBP management. The method used is descriptive qualitative, and data collection is done through direct observation, interviews, and documentation. The results of this study indicate that the application of the concept of interoperability utilizing web service technology has succeeded in supporting the process of exchanging and sharing data between the applications involved properly and smoothly. This study concludes that the use of the Aplikasi Mandiri in managing SKBP has succeeded in shortening the issuance time of SKBP and cutting bureaucratic lines in the library. The time efficiency offered contributes to increasing the productivity of students and officers involved.